2012
DOI: 10.1177/1368430212468170
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive costs of contemporary prejudice

Abstract: Two studies examined the cognitive costs of blatant and subtle racial bias during interracial interactions. In Study 1, Black participants engaged in a 10-minute, face-to-face interaction with a White confederate who expressed attitudes and behaviors consistent with blatant, subtle, or no racial bias. Consistent with contemporary theories of modern racism, interacting with a subtly biased, compared with a blatantly biased, White partner impaired the cognitive functioning of Blacks. Study 2 revealed that Latino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…These findings are consistent with previous research that found no association between racial/ethnic discrimination and lifetime substance use disorders [5, 24]. These findings are also in line with theoretical and empirical works [32, 33] that suggest that it is the more subtle and ambiguous forms of discrimination, rather than the overt or specific (race/ethnic-related) type, that is more likely to be internalized and thereby result in worse cognitive and behavioral effects.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with previous research that found no association between racial/ethnic discrimination and lifetime substance use disorders [5, 24]. These findings are also in line with theoretical and empirical works [32, 33] that suggest that it is the more subtle and ambiguous forms of discrimination, rather than the overt or specific (race/ethnic-related) type, that is more likely to be internalized and thereby result in worse cognitive and behavioral effects.…”
Section: Discussionsupporting
confidence: 92%
“…Crocker and Major [32] theorize that discrimination that is not ambiguous and more clearly attributed to racial/ethnic factors is less likely to be internalized and more likely attributed to broader structural factors (e.g., “system blame”) instead of toward the self. For example, in an experimental study, Latino college students who viewed an interracial interaction where a White person was subtly biased experienced cognitive costs (i.e., impairment during the Stroop task) compared to those exposed to a White person who expressed blatant or no racial bias [33]. This study suggests that everyday discrimination may have a more deleterious effect than racial/ethnic discrimination, given the subtle and ambiguous nature of everyday discrimination, which may make it more difficult to discern and respond to than experiences of discrimination about which one is certain are attributed to one’s race/ethnicity [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the women in our studies may have been especially likely to feel threatened by and react against this type of blatant group-level discrimination. Indeed, it is unclear whether perceiving personal discrimination, especially if it is more subtle and ambiguous than the sexism described in the articles used in the present work, would engender similar results (e.g., Murphy, Richeson, Shelton, Rheinschmidt, & Bergsieker, 2011;Operario & Fiske, 2001). It is also important to point out that the present research examined the effects of making chronic, pervasive sexism salient on evaluations of stigmatized outgroups.…”
Section: Limitationsmentioning
confidence: 75%
“…In other research drawing on attributional ambiguity theory (Crocker, & Major, ; Major & Crocker, ), Murphy et al. (, Study 1) directly manipulated the behavior of a White interaction partner to investigate whether experiencing subtle bias would impair minorities’ cognitive functioning. In the study, Black participants interacted with a White confederate who was trained to express subtle bias or no bias during the interaction.…”
Section: Executive Functionsmentioning
confidence: 99%